2016
DOI: 10.1017/s1368980015003778
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of cooking and the implications for cooking behaviour in the USA

Abstract: Objective: Despite the importance of cooking in modern life, public perceptions about what it means to cook are unknown. We aimed to examine perceptions of cooking and their association with cooking confidence, attitudes and behaviours in the USA. Design: We designed and fielded a nationally representative survey among US adults (n 1112) in April 2015. We used factor analysis to identify perceptions about cooking and multivariate ordered logit and Poisson models to explore associations between those perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 33 publications
(45 reference statements)
1
47
2
Order By: Relevance
“…Use of incentives or other monitoring tools, such as social media, should be researched to improve reporting of these data, as should strategies to increase parent involvement in supporting cooking at home as noted by Fordyce-Voordam. 54 Additionally, while several studies measured confidence and perceived self-efficacy in cooking skills or attitudes toward cooking, [55][56][57][58] no method for measuring actual cooking skills in youth has been validated other than through direct observation, which may be unfeasible depending on sample size and constraints of the classroom setting. Development of such a method would constitute a significant contribution to the literature in this domain due to limitations of using measures of perceived ability as a proxy for actual ability.…”
Section: Discussionmentioning
confidence: 99%
“…Use of incentives or other monitoring tools, such as social media, should be researched to improve reporting of these data, as should strategies to increase parent involvement in supporting cooking at home as noted by Fordyce-Voordam. 54 Additionally, while several studies measured confidence and perceived self-efficacy in cooking skills or attitudes toward cooking, [55][56][57][58] no method for measuring actual cooking skills in youth has been validated other than through direct observation, which may be unfeasible depending on sample size and constraints of the classroom setting. Development of such a method would constitute a significant contribution to the literature in this domain due to limitations of using measures of perceived ability as a proxy for actual ability.…”
Section: Discussionmentioning
confidence: 99%
“…A web-based survey to measure cooking skills, food skills, food agency, cooking attitudes, perceptions about the meaning of cooking, cooking confidence, cooking behavior, and dietary intake was designed. All cooking-related scales and measures were taken from previously validated surveys [22,24,28]. Because the cooking skills and food skills measures had not been validated in a US sample, we conducted "think aloud" cognitive interviews (n = 10) to ensure they were understood as intended and adjusted any wording for a US audience.…”
Section: Methodsmentioning
confidence: 99%
“…These scales have expanded the number and types of skills considered important for home cooking and have shown that both cooking and food skills are critical for shaping dietary intake [23]. Other measures of cooking confidence and attitudes as well as how people perceive what it means to cook (related to the role of convenience foods vs. scratch ingredients and whether heat is required for cooking) have also been shown to be important predictors of cooking behavior [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The instrument combined previously validated questionnaires of sociodemographic variables , household food security and household food preparation equipment . Human nutrition professionals pilot tested the instrument for comprehension and length, without changes to the text or time for completion.…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic variables included age, sex, ethnicity, highest level of education completed, annual household income, food assistance programmes utilised, household size, marital status and primary food preparer . Self‐reported height (feet, inches) and weight (pounds) were queried, and investigators used height and weight data to calculate the body mass index (BMI; kg m −2 ) of each respondent.…”
Section: Methodsmentioning
confidence: 99%